Exosomes from human umbilical cord mesenchymal stem cells enhance fracture healing through HIF‐1α‐mediated promotion of angiogenesis in a rat model of stabilized fracture. (20th January 2019) - Zhang, Yuntong; Hao, Zichen; Wang, Panfeng; Xia, Yan; Wu, Jianghong; Xia, Demeng; Fang, Shuo; Xu, Shuogui
Abstract: Objectives: Exosomes, as important players in intercellular communication due to their ability to transfer certain molecules to target cells, are believed to take similar effects in promoting bone regeneration with their derived stem cells. Studies have suggested that umbilical cord mesenchymal stem cells (uMSCs) could promote angiogenesis. This study investigated whether exosomes derived from uMSCs (uMSC‐Exos) could enhance fracture healing as primary factors by promoting angiogenesis. Materials and Methods: uMSCs were obtained to isolate uMSC‐Exos by ultrafiltration, with exosomes from human embryonic kidney 293 cells (HEK293) and phosphate‐buffered saline (PBS) being used as control groups. NanoSight, laser light scattering spectrometer, transmission electron microscopy and Western blotting were used to identify exosomes. Next, uMSC‐Exos combined with hydrogel were transplanted into the fracture site in a rat model of femoral fracture. Bone healing processes were monitored and evaluated by radiographic methods on days 7, 14, 21 and 31 after surgery; angiogenesis of the fracture sites was assessed by radiographic and histological strategies on post‐operative day 14. In vitro, the expression levels of osteogenesis‐ or angiogenesis‐related genes after being cultured with uMSC‐Exos were identified by qRT‐PCR. The internalization ability of exosomes was determined using the PKH67 assay. Cell cycle analysis, EdU incorporation and immunofluorescence staining, scratch wound assay and tube formation analysis were also used to determine the altered abilities of human umbilical vein endothelial cells (HUVECs) administered with uMSC‐Exos in proliferation, migration and angiogenesis. Finally, to further explore the underlying molecular mechanisms, specific RNA inhibitors or siRNAs were used, and the subsequent effects were observed. Results: uMSC‐Exos had a diameter of approximately 100 nm, were spherical, meanwhile expressing CD9, CD63 and CD81. Transplantation of uMSC‐Exos markedly enhanced angiogenesis and bone healing processes in a rat model of femoral fracture. In vitro, other than enhancing osteogenic differentiation, uMSC‐Exos increased the expression of vascular endothelial growth factor (VEGF) and hypoxia inducible factor‐1α (HIF‐1α). uMSC‐Exos were taken up by HUVECs and enhanced their proliferation, migration and tube formation. Finally, by using specific RNA inhibitors or siRNAs, it has been confirmed that HIF‐1α played an important role in the uMSC‐Exos‐induced VEGF expression, pro‐angiogenesis and enhanced fracture repair, which may be one of the underlying mechanisms. Conclusions: These results revealed a novel role of exosomes in uMSC‐mediated therapy and suggested that implanted uMSC‐Exos may represent a crucial clinical strategy to accelerate fracture healing via the promotion of angiogenesis. HIF‐1α played an important role in this process. Abstract : Exosomes from human umbilical cord mesenchymal stem cells enhance fracture healing through HIF‐1α‐mediated promotion of angiogenesis in a rat model.